Deux agents littéraires dans le siècle américain William et Jenny Bradley, passeurs culturels transatlantiques - Cossu-Beaumont, Laurence (Métamorphoses du livre, 2023)
Who introduced the great American writers to French readers in the interwar years? Who contributed to the circulation of French literature in the United States? The mediators involved in these transatlantic transfers included two lesser-known figures: William and Jenny Bradley. As founders of the first literary agency in France, the Bradleys represented authors such as Clemenceau, Cendrars, Colette, Gide, Malraux, Sartre and Camus, and also Dreiser, Hemingway, Faulkner, Stein, Dos Passos, Chandler, and Baldwin. This study draws on previously unexplored archival material to unveil the fascinating story of this French-American couple and shed new light on literary history, the history of books and the history of publishing, from the 1920s to the immediate post-war years. The narrative offers encounters with the main players in the book industry and delves into the social world of the salons, taking the reader from the Parisian Left Bank to the Riviera, and then on to the shores of America, the destination of transatlantic ships carrying books, letters and travellers.